Ratio of Elements Carbon (C), Nitrogen (N), and Phosphorus (P) At Sediment in Seagrass Ecosystem Nirwana Beach Padang West Sumatera - Silitonga, May Sarah; Nedi, Syahril; Zulkifli, Zulkifli (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was conducted in November 2020 at Nirwana Beach, Teluk Bayur, Padang City, West Sumatra Province. The organic carbon concentration in the sediments at Nirwana Beach ranges from 1.0320 – 3.03550%, the nitrate content ranges from 0.8599– 0.9577 mg/L, the phosphate 1.8231– 2.7616 mg/L. The C:N:P ratio of sediment is 18.75:1:2.25. The type of sediment found in this study is gravel-sand and seagrass found in the research location was Thalassia hemprichii with a density of 105 - 312 stands/m2. The correlation between the concentration of organic carbon, nitrate, and phosphate on the density of seagrass species is positive.